The Fabulist’s Art Some Brief Remarks on Solomon’s Lions (1 Kings 10:18-20) With a Minor Reception History - Waller, Daniel James (2016)
In his description of King Solomon’s throne in 1 Kgs 10:19-20, the author of this passage employs two different plural endings (one masculine and one feminine) of the lions which line the steps of this throne. The present work suggests that a semantic distinction is intended by the use of these two different forms. It considers the wider aesthetic project of 1 Kgs 9:10-10:29 and suggests that, in light of this project, we may fruitfully consider interpreting these lions as living creatures. It then turns to several midrashic passages which lend some support to this interpretation.
Keywords: Bibel